2012
DOI: 10.2298/sgs1201022d
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of caries and gingivitis among school children in the municipality of Foca

Abstract: Oral health is an integral part of general health and can significantly affect the quality of life [1, 2]. The prevalence of oral diseases is high and their impact on an individual and a community is significant [3]. Dental caries is one of the most common chronic diseases today, occurring in 60-90% of school children and many adults [1]. It should be noted that caries in children has not been completely eradicated, but has been put under control only to a certain extent [4]. Recent research has shown a signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2012
2012
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
1
0
1
Order By: Relevance
“…The mean DMFT value among adolescents age 1618 years was about 8.6. Djordjevic et al [9] reported slightly higher value of the DMFT index 9.5 in adolescents age 1718 years in the municipality of Foca, Republika Srpska. On the other hand, lower values of the index were observed in studies of Hugo et al [10] where the DMFT value was 5.5 in adolescents age 1518 years, as well as in the study of Xhemnica et al [11] where the mean value of this index was about 5.7 in adolescents age 1718 years.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The mean DMFT value among adolescents age 1618 years was about 8.6. Djordjevic et al [9] reported slightly higher value of the DMFT index 9.5 in adolescents age 1718 years in the municipality of Foca, Republika Srpska. On the other hand, lower values of the index were observed in studies of Hugo et al [10] where the DMFT value was 5.5 in adolescents age 1518 years, as well as in the study of Xhemnica et al [11] where the mean value of this index was about 5.7 in adolescents age 1718 years.…”
Section: Discussionmentioning
confidence: 95%
“…Sred nja vred nost in dek sa KEP kod ado le sce na ta uz ra sta 16-18 go di na bi la je oko 8,6. U is tra ži va nju Đor đe vi će ve i sa rad ni ka [9] za be le že na je ne što ve ća vred nost ovog in dek sa (oko 9,5) kod uče ni ka uz ra sta od 17 i 18 go di na na pod ruč ju op šti ne Fo ča, u Re pu bli ci Srp skoj. S dru ge stra ne, ni že vred no sti in dek sa utvr đe ne su u is tra ži va nji ma Hu ga (Hu go) i sa rad ni ka [10], u ko ji ma je vred nost in dek sa KEP bi la 5,5 kod ado le sce na ta uz ra sta 15-18 go di na, kao i u stu di ji Ksem ni ke (Xhem ni ca) i sa rad ni ka [11], gde je sred nja vred nost ovog in dek sa bi la oko 5,7 kod ado le sce na ta uz ra sta 17-18 go di na.…”
Section: Rezultatiunclassified